Phase II study of Radium‐223 dichloride combined with hormonal therapy for hormone receptor‐positive, bone‐dominant metastatic breast cancer. (18th December 2019) - Ueno, Naoto T.; Tahara, Rie K.; Fujii, Takeo; Reuben, James M.; Gao, Hui; Saigal, Babita; Lucci, Anthony; Iwase, Toshiaki; Ibrahim, Nuhad K.; Damodaran, Senthil; Shen, Yu; Liu, Diane D.; et al.
Abstract: Background: Radium‐223 dichloride (Ra‐223) is a targeted alpha therapy that induces localized cytotoxicity in bone metastases. We evaluated the efficacy and safety of Ra‐223 plus hormonal therapy in hormone receptor‐positive (HR+), bone‐dominant metastatic breast cancer. Methods: In this single‐center phase II study, 36 patients received Ra‐223 (55 kBq/kg intravenously every 4 weeks) up to 6 cycles with endocrine therapy. The primary objective was to determine the clinical disease control rate at 9 months. Secondary objectives were to determine (a) tumor response rate at 6 months, (b) progression‐free survival (PFS) durations, and (c) safety. Results: The median number of prior systemic treatments for metastatic disease was 1 (range, 0‐4). The disease control rate at 9 months was 49%. The tumor response rate at 6 months was 54% (complete response, 21%; partial, 32%). The median PFS was 7.4 months (95% CI, 4.8‐not reached [NR]). The median bone‐PFS was 16 months (95% CI, 7.3‐NR). There were no grade 3/4 adverse events. Conclusions: Ra‐223 with hormonal therapy showed possible efficacy in HR+ bone‐dominant breast cancer metastasis, and adverse events were tolerable. We plan to further investigate the clinical application of Ra‐223 in these patients. (NCT02366130). Abstract : Radium‐223 dichloride is a targeted alpha therapy with localized cytotoxicity for bone metastasis.Our phase II trial which tested radium‐223 dichloride combined with hormonal therapy provided a high disease control with minimum toxicity in patients with hormone receptor‐positive, bone‐dominant metastatic breast cancer.